Essential Elements of Special Education Classroom Administration - Dathong, Supatchaya; Wannawan, Panithan; Sukserm, Pennapa (Journal of Green Learning, 2024)
This research aims to examine the essential elements of special education classroom administration which was conducted in 3 steps by reviewing 15 sources of related documents and research to synthesize the essential elements of special education classroom administration, exploring the developmental essential elements of special education classroom administration through in-depth interviews in 2 cases, using purposive sampling, particularly special education centers that received the IQA AWARD for excellence in the academic year 2023, and surveying the needs for managing special education classrooms, examining current problems, needs, and analyzing the necessity using the Modified Priority Needs Index (PNI modified). For data collection and content analysis, research instruments included in-depth, semi-structured interviews and a researcher-developed questionnaire. The findings revealed six components of special education classroom management: psychological environmental arrangement, physical environmental arrangement, participation in classroom management, social environmental arrangement, teacher leadership, and learner-centered learning management.